Pengaruh Media Sosial Akun Instagram @Jjs_Pangkepp terhadap Minat Berkunjung Followers ke Objek Wisata Pangkep - Musdalifah Musdalifah; Sabaruddin Machmud; Raidah Intizar Yusuf (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2021)
This study aims to find out how the influence of social media on the Instagram account @jjs_pangkepp on followers'interest in visiting Pangkep tourism objects. The type of research used is quantitative research with data collectiontechniques through surveys with data analysis Multiple Linear Regression Analysis using SPSS version 20.The results showed that the influence of social media on the Instagram account @jjs_pangkepp gave a strong andsignificant positive influence on followers' interest in visiting the Pangkep tourist attraction, the magnitude of theinfluence given was 61.2% with a sig level. 0.000 < 0.005. While the remaining 38.8% is influenced by other factors.